Rules on ecological zoning in the modern system of law of the Republic of Kazakhstan (Journal of actual problems of jurisprudence, 2019)
The main issue of the article is the place of the rules on ecological zoning in the modern system of law of the Republic ofKazakhstan. The notion of Ecological Law was described and formation of sub-institution called “Ecological Zoning”was analyzed. The sub-institution was scrutinized by studying its subjects, objects, methods and connection with otherinstitutions and sub-institutions of Ecological Law.Key words: ecological law; ecological zoning; rules on ecological zoning.